ABOUT NATURAL AND ARTIFICIAL INTELLIGENCE OF CYBERNETIC SYSTEMS - Серій Ілліч Доценко (Радіоелектронні і комп'ютерні системи, 2019)
It is proposed as part of the concept of the “cybernetic system” to distinguish the following components: - cybernetic systems impervious to information, as a control system; - cybernetic systems permeable to information: intelligent functional systems based on natural intelligence; Intelligent information systems based on artificial intelligence. From an analysis of the content of the concept of “artificial intelligence,” it follows that at present there is no unambiguous definition of the content of this concept. Almost all authors agree that artificial intelligence should be similar to human intelligence. From an analysis of the content of the concept of “natural intelligence,” it follows that its basis is the central regularity of the integrative activity of the brain. It is proposed to define thinking as the possibility of representing things in measure, and intelligence as the ability to implement the process of measuring things. The measure is the presentation of a thing in the form of a dialectical unity of concepts general (qualitative definition) – single (quantitative definition). It is shown that the main problem that has not been solved so far for artificial neural networks is the problem of the formation of a capable mathematical model of a natural neuron based on the central regularity of integrative brain activity. The second problem requiring its solution is the need to teach the artificial intelligence system to "measure" things, as well as their properties. Without mastering this ability, no artificial intelligence system can implement the actions that characterize the activity of the natural neural network. The third problem is the need to train the artificial intelligence system to remember the previous experience. Manipulating knowledge is possible only by applying the laws of natural intelligence. Therefore, to form the knowledge base, experts are involved as a source of knowledge and knowledge engineers, as specialists in the extraction of knowledge from experts. Moreover, between the concepts of “data” and “information”, as well as “information” and “knowledge”, there is a dialectical connection in the form of “single” – “general”. Intelligent information technology can be the basis for the implementation of cybernetic systems permeable to information: intelligent functional systems; intelligent information systems. The fundamental task that needs to be solved is the task of establishing the composition and content of the concept of “unit of knowledge”.